Doping β-Ga2O3 with europium: influence of the implantation and annealing temperature. (18th July 2017) - Peres, M; Lorenz, K; Alves, E; Nogales, E; Méndez, B; Biquard, X; Daudin, B; Víllora, E G; Shimamura, K
Abstract: β -Ga2 O3 bulk single crystals were doped by ion implantation at temperatures from room temperature to 1000 °C, using a 300 keV Europium beam with a fluence of 1  ×  10 15 at cm −2 . Rising the implantation temperature from room temperature to 400–600 °C resulted in a significant increase of the substitutional Eu fraction and of the number of Eu ions in the 3+  charge state as well as in a considerable decrease of implantation damage. Eu is found in both charge states 2+  and 3+  and their relative fractions are critically dependent on the implantation and annealing temperature, suggesting that defects play an important role in stabilizing one of the charge states. The damage recovery during post-implant annealing is a complex process and typically defect levels first increase for intermediate annealing temperatures and a significant recovery of the crystal only starts around 1000 °C. Cathodoluminescence spectra are dominated by the sharp Eu 3+ related intra-ionic 4f transition lines in the red spectral region. They show a strong increase of the emission intensity with increasing annealing temperature, in particular for samples implanted at elevated temperature, indicating the optical activation of Eu 3+ ions. However, no direct correlation of emission intensity and Eu 3+ fraction was found, again pointing to the important role of defects on the physical properties of these luminescent materials.